THE ROLE OF SOCIAL SUPPORT ON DUAL ROLE CONFLICT IN WOMENPRENEURS IN GARUT DISTRICT - Nurhasan, Rohimat; Munawar, Soviyan; Maulidiani, Alda; Munawi, Ahmad Syarif (Fakultas Ekonomi Universitas Garut, 2024)
The role of women in life has undergone significant changes. Today, women have equal rights to work. Women who perform the role of a housewife while working are often referred to as women with dual roles. However, carrying out dual roles often causes pressure and feelings of inadequacy in fulfilling all these demands. In this case, social support is important in helping working women deal with the pressures of work and family. Social support can enable them to work actively and provide a positive attitude and good contribution to both. This study aims to determine the extent to which social support provided by family, friends, co-workers, and the government is able to improve the time management skills, attitudes, and emotions of womenpreneurs in Food Stalls in Garut Regency. This study uses quantitative methods with primary data obtained through distributing questionnaires to 106 womenpreneurs. The sample selection was carried out using accidental sampling technique. Data analysis was conducted using the PLS-SEM method through two main tests, namely the outer model and inner model. The results showed that social support provided to womenpreneurs was able to improve their ability to manage time, manage emotions, and form positive attitudes. Thus, social support is proven to have a positive influence on dual role conflict.